Relationship between Teachers’ Knowledge of Air Pollution and Personal Hygiene Promotion Strategy - Hidayatur Rokhmah; Yuli Kurniawati Sugiyo Pranoto; Ali Formen (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
Bahasa Indonesia:a Kindergarten teachers’ knowledge of air pollution is important because air pollution may negatively affect young children’s health. Teachers need adequate understanding to implement appropriate personal hygiene promotion strategies in early childhood education settings. However, studies examining the relationship between teachers’ knowledge of air pollution and personal hygiene promotion strategies remain limited. This study aims to analyze the relationship between teachers’ knowledge about air pollution and personal hygiene promotion strategies for early childhood children. This study employed a quantitative approach with a survey research design. The research subjects consisted of kindergarten teachers selected through a quota sampling technique. Data were collected using a survey method with questionnaires distributed both offline and online. Data analysis was conducted through validity testing, reliability testing, normality testing, and Pearson Product Moment analysis to examine the relationship between the research variables. The results revealed a positive relationship between teachers’ knowledge about air pollution and personal hygiene promotion strategies. Teachers with better understanding of the impacts of air pollution tended to implement more effective personal hygiene promotion strategies for early childhood children. The conclusion of this study indicates that teachers’ knowledge plays an important role in shaping educational strategies related to children’s personal hygiene as an effort to prevent the negative effects of air pollution. The implications of this study emphasize the importance of strengthening teachers’ knowledge regarding enviroa Kindergarten teachers’ knowledge of air pollution is important because air pollution may negatively affect young children’s health. Teachers need adequate understanding to implement appropriate personal hygiene promotion strategies in early childhood education settings. However, studies examining the relationship between teachers’ knowledge of air pollution and personal hygiene promotion strategies remain limited. This study aims to analyze the relationship between teachers’ knowledge about air pollution and personal hygiene promotion strategies for early childhood children. This study employed a quantitative approach with a survey research design. The research subjects consisted of kindergarten teachers selected through a quota sampling technique. Data were collected using a survey method with questionnaires distributed both offline and online. Data analysis was conducted through validity testing, reliability testing, normality testing, and Pearson Product Moment analysis to examine the relationship between the research variables. The results revealed a positive relationship between teachers’ knowledge about air pollution and personal hygiene promotion strategies. Teachers with better understanding of the impacts of air pollution tended to implement more effective personal hygiene promotion strategies for early childhood children. The conclusion of this study indicates that teachers’ knowledge plays an important role in shaping educational strategies related to children’s personal hygiene as an effort to prevent the negative effects of air pollution. The implications of this study emphasize the importance of strengthening teachers’ knowledge regarding environmental health and personal hygiene through training and continuous educational programs to support the development of clean and healthy living habits in early childhood. nmental health and personal hygiene through training and continuous educational programs to support the development of clean and healthy living habits in early childhood. Anak-anak sangat rentan terhadap polusi udara, terutama pada masa awal kehidupan mereka dan bahkan selama masa pertumbuhan janin, karena paru-paru, otak, organ, dan sistem kekebalan tubuh mereka belum matang. Pada anak usia prasekolah, personal hygiene memiliki peran yang sangat penting untuk memelihara kesehatan dan kebersihan sehingga fisik maupun psikisnya sejahtera. Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan guru tentang polusi udara dengan strategi promosi personal hygiene. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian survei. Teknik pengambilan sampel menggunakan teknik quota sampling. Berdasarkan perhitungan jumlah sampel menggunakan rumus Slovin dan didapat jumlah sampel berjumlah 95 guru. Dari uji pearson product moment, didapatkan bahwa nilai signifikansi 2-tailed yaitu 0,012. Kemudian hubungan pengetahuan guru tentang polusi udara dengan strategi promosi personal hygiene yaitu berhubungan positif (berkorelasi positif) karena pada nilai pearson correlation mendapatkan hasil sebesar 0,256. Jadi dapat disimpulkan bahwa ada hubungan positif antara pengetahuan guru tentang polusi udara dengan strategi promosi personal hygiene.   Bahasa Inggris: Children are particularly vulnerable to air pollution, especially in their early life and even during fetal development, as their lungs, brain, organs and immune system are immature. In preschool-aged children, personal hygiene has a very important role to maintain health and hygiene so that they are physically and psychologically well. This study aims to determine the relationship between teacher knowledge about air pollution and personal hygiene promotion strategies. This research is a quantitative study with a survey research design. The sampling technique used quota sampling technique. Based on the calculation of the number of samples using the Slovin formula and obtained a sample size of 95 teachers. From the Pearson product moment test, it was found that the 2-tailed significance value was 0.012. Then the relationship between teacher knowledge about air pollution and personal hygiene promotion strategies is positively related (positively correlated) because the pearson correlation value gets a result of 0.256. So it can be concluded that there is a positive relationship between teacher knowledge about air pollution and personal hygiene promotion strategies.